(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article analyzes the foreign trade turnover of the national economy, the share of exports and imports, and the balance between them. Also, the development trend of the foreign trade process and its possibilities to strengthen the country’s position in the world market are shown.